2011
DOI: 10.5751/es-04275-160315
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical and Socioeconomic Factors Associated with Forest Transitions at Multiple Spatial and Temporal Scales

Abstract: ABSTRACT. Forest transitions (FT) occur when socioeconomic development leads to a shift from net deforestation to reforestation; these dynamics have been observed in multiple countries across the globe, including the island of Puerto Rico in the Caribbean. Starting in the 1950s, Puerto Rico transitioned from an agrarian to a manufacturing and service economy reliant on food imports, leading to extensive reforestation. In recent years, however, net reforestation has leveled off. Here we examine the drivers of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 33 publications
6
50
0
2
Order By: Relevance
“…Three out of four reforestation hotspots were located in the highland forests of the Andes mountain range. Other studies have also detected forest regeneration in mountainous areas (Yackulic et al 2011, which are less suitable for mechanized agriculture. Our reforestation hotspots coincide with other studies that have identified forest recovery in the Andes (Cardenas 2000, Cabrera et al 2011, Rodríguez et al 2012 and in the Amazon foothills (Etter et al 2006a, Dávalos et al 2011) of Colombia.…”
Section: Factors Explaining Land Change Within Hotspotsmentioning
confidence: 99%
“…Three out of four reforestation hotspots were located in the highland forests of the Andes mountain range. Other studies have also detected forest regeneration in mountainous areas (Yackulic et al 2011, which are less suitable for mechanized agriculture. Our reforestation hotspots coincide with other studies that have identified forest recovery in the Andes (Cardenas 2000, Cabrera et al 2011, Rodríguez et al 2012 and in the Amazon foothills (Etter et al 2006a, Dávalos et al 2011) of Colombia.…”
Section: Factors Explaining Land Change Within Hotspotsmentioning
confidence: 99%
“…Recent studies suggest that FT is associated with variables related to socioeconomic development, such as rural abandonment and accompanying urbanization, agricultural intensification, the establishment of extensive tree plantations (often through statedriven policies), economic industrialization, growing education and technical knowledge, and the strengthening of sociopolitical institutions (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). However, these studies, including the seminal descriptions of FT in Europe (21)(22)(23)(24)(25) and Southeast Asia (10,26), are mostly derived from case studies of a single country, usually because data are only available at the national level, which limits the potential for broad-scale extrapolation or generalization of findings and has strong potential for biases because of arbitrary or opportunistic site selection (27).…”
mentioning
confidence: 99%
“…Determining whether and where a forest transition occurs depends on large-scale analyses of which regions become production landscapes to provide commodities for distal consumption and which regions become consumption landscapes. For example, Walker [31], Pfaff & Walker [32], Meyfroidt & Lambin [33] and Yackulic et al [34] explain forest transitions in Brazil's Atlantic Forest, northeastern USA, Vietnam and Puerto Rico, respectively, through each location's distal connections with production landscapes.…”
Section: Introductionmentioning
confidence: 99%